A machine learning framework for automated text categorization - Bong, Chih How (Faculty of Computer Science and Information Technology, 2001)
This dissertation describes a machine learning framework for the development of an automated text categorization system for real-life problems. Conference paper classification will be used as a case study of a life text categorization problem. Unlike documents in benchmark collections, text documents such as conference papers tend to be rather heterogeneous having a rich structure with variable length documents where each category consists of a variable number of documents.